2013
DOI: 10.1103/physreve.88.032601
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glass transition temperature in multilayered poly(methyl methacrylate) thin film supported on a Si substrate as studied by neutron reflectivity

Abstract: We studied the distribution of glass transition temperature (Tg) through neutron reflectivity in a poly(methyl methacrylate) (PMMA) thin film supported on a silicon substrate with a five-layered PMMA thin film consisting of deuterated-PMMA and hydrogenated-PMMA. The depth distribution of Tg was successfully observed in the PMMA thin film. Compared to the previously reported distribution of Tg in a polystyrene thin film, the presence of a long-range interfacial effect, supposedly caused by an interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…This must be due to the interfacial hard layer near the substrate because of strong interactions between the PMMA and the Si surface. These results as well as recent intensive studies [22][23][24][25][26][27][28][29] suggest that polymer thin films have very heterogeneous dynamics or structure along the depth direction, consisting of a surface mobile layer, a middle bulklike layer, and an interfacial hard layer.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This must be due to the interfacial hard layer near the substrate because of strong interactions between the PMMA and the Si surface. These results as well as recent intensive studies [22][23][24][25][26][27][28][29] suggest that polymer thin films have very heterogeneous dynamics or structure along the depth direction, consisting of a surface mobile layer, a middle bulklike layer, and an interfacial hard layer.…”
Section: Introductionsupporting
confidence: 62%
“…We have performed neutron reflectivity measurements on five-layer PS and PMMA thin films consisting of alternatively stacked deuterated PS (dPS) and hydrogenated PS (hPS) (or PMMA) layers (dPS/hPS/dPS/hPS/dPS) [27] (or dP-MMA/hPMMA/dPMMA/hPMMA/dPMMA) [28] to evaluate the heterogeneous dynamics of thin films directly. In these experiments, we have evaluated the thickness of each layer * Present address: Institute for Chemical Research, Kyoto University, Uji, Kyoto 611-0011, Japan; kanaya@scl.kyoto-u.ac.jp as a function of temperature and estimated T g of each layer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the glass transition temperature near the surface of the glasses varies from that of the bulk. For example, glass transition temperatures found in a surface layer approximately 1000 Å thick in poly(methyl methacrylate) films differ from those of the bulk . Yu and coworkers reported that diffusion on the surface of glasses was at least 10 6 times faster than bulk diffusion, and glass surface diffusion can cause surface evolution at nm to μm scale, which is a length scale that would be expected to be long enough for (conformationally perturbed) protein molecules to collide with each other in the surface glass layer, causing aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in this field has produced a multitude of research, and we refer the reader to several studies and review articles to gain a broader appreciation for the subject . Positron annihilation lifetime spectroscopy (PALS) and neutron reflectivity have also been used to characterize thin film T g . Although the majority of experimental studies attribute confined T g behavior to strong interfacial influences, these studies relied on models and indirect measurements of local T g to support their conclusions .…”
Section: Confined Polymer Propertiesmentioning
confidence: 99%